Diplodia corticola and Phytophthora cinnamomi: the main pathogens involved in holm oak decline on Caprera Island (Italy). Issue 3 (4th December 2013) - Linaldeddu, B. T.; Scanu, B.; Maddau, L.; Franceschini, A.; Belbahri, L.
Summary Since 2008, severe and widespread tree decline and mortality has been observed at the main growing Quercus ilex L. (holm oak) forest on Caprera Island, Italy. To clarify the symptomatology and aetiology of this phenomenon, field surveys and isolations from symptomatic trees were carried out in summer 2010. Affected trees exhibited crown thinning, branch dieback, sunken cankers, epicormic shoots, exudates on branches and trunk, root losses and sudden death symptoms. Four fungal species belonging to Botryosphaeriaceae family, namely Botryosphaeria dothidea, Diplodia corticola, D. seriata and Neofusicoccum parvum, were isolated from cankers on trunk and branches, whereas three species of Phytophthora, namely P. cinnamomi, P. cryptogea and P. gonapodyides, were isolated from fine roots and rhizosphere soil samples. Isolates were identified using both morphological analysis and DNA‐based techniques. Pathogenicity trials on holm oak seedlings showed that all the isolated species are pathogenic. D. corticola proved to be the most aggressive species. Our results provide the first evidence for a combined involvement of D. corticola and P. cinnamomi in the aetiology of holm oak decline in Italy and suggest that these pathogens are not only important contributing factors in the onset of long‐term tree decline, but also may cause the rapid devastation of extensive oak ecosystems.